2003
DOI: 10.1046/j.1469-8137.2003.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Source–sink balance and carbon allocation below ground in plants exposed to ozone

Abstract: Contents Summary 213 Introduction 213 Source–sink model: carbohydrate signaling 214 Effect of ozone on above‐ground sources and sinks 216 Decreased allocation below ground 218 Carbon flux to soils 220 Soil food web 223 Summary, conclusions and future research 223 Acknowledgements 223 References 223 Summary The role of tropospheric ozone in altering plant growth and development has been the subject of thousands of publications over the last several decades. Still, there is limited understanding regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
368
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(393 citation statements)
references
References 172 publications
(224 reference statements)
21
368
3
1
Order By: Relevance
“…Also in Quercus pyrenaica, root biomass (and the ratio between above-ground and root biomass) was more importantly affected than above-ground biomass. Ozone effects on roots and/or on the above-mentioned ratio have been reported as a consequence of reduction in CO 2 assimilation but also of photoassimilate allocation from source tissues (leaves) to sink tissues (roots) (Andersen, 2003). Under natural conditions, root reduction and changes in biomass partitioning in tree species may reduce resistance to windthrow (Broadmeadow and Jackson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Also in Quercus pyrenaica, root biomass (and the ratio between above-ground and root biomass) was more importantly affected than above-ground biomass. Ozone effects on roots and/or on the above-mentioned ratio have been reported as a consequence of reduction in CO 2 assimilation but also of photoassimilate allocation from source tissues (leaves) to sink tissues (roots) (Andersen, 2003). Under natural conditions, root reduction and changes in biomass partitioning in tree species may reduce resistance to windthrow (Broadmeadow and Jackson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…EO 3 not only causes losses to crop yield but can also significantly reduce the allocation of assimilates into the root. This reduction in root biomass would influence the entry of organic matter into the soil (Andersen, 2003). EO 3 reduces litter quality and rates of decay.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the US National Crop Loss Assessment Network (NCLAN) and European Open Top Chamber Programme (EOTCP) have shown significant yield losses of major crops in USA and Europe. Investigations of crop responses to elevated O 3 concentration in terms of phenology, physiology, production and yield have confirmed that elevated O 3 could accelerate crop senescence, decrease photosynthesis, reduce biomass and carbon allocation into roots, and cause yield loss (Morgan et al, 2003;Andersen, 2003;Fiscus et al, 2005;Ashmore, 2005;Feng et al, 2008;Feng and Kobayashi, 2009). Although there are differences in O 3 sensitivity among crops, there are a considerable number of crops sensitive to elevated O 3 concentrations and subject to yield loss.…”
Section: Introductionmentioning
confidence: 99%